Primary percutaneous coronary intervention for ST elevation myocardial infarction in octogenarians: trends and outcomes. Issue 11 (4th December 2009) - Claessen, Bimmer E P M; Kikkert, Wouter J; Engstrom, Annemarie E; Hoebers, Loes P C; Damman, Peter; Vis, Marije M; Koch, Karel T; Baan, Jan; Meuwissen, Martijn; J van der Schaaf, René; de Winter, Robbert J; Tijssen, Jan G P; et al.
Abstract : Objective: The general population is gradually ageing in the western world. Therefore, the number of octogenarians undergoing primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) is increasing. We aim to provide insight into temporal trends in the annual proportions of octogenarians among STEMI patients undergoing primary PCI and their clinical characteristics and outcomes over an 11-year observational period. Design: Single-centre observational study. Patients: Between 1997 and 2007, 4506 STEMI patients were treated with primary PCI at the authors' institution. Patients aged over 80 years were identified. Main outcome measures: Temporal trends in the annual proportion of octogenarian STEMI patients and their baseline characteristics, 30-day and 1-year mortality were analysed. Results: A total of 379 octogenarians (8.4% of the total population) was treated with primary PCI between 1997 and 2007. Over time, the annual proportion of octogenarians gradually increased from four of 113 (3.5%) in 1997 to 51 of 579 (8.8%) in 2007 (p for trend <0.01). In the total cohort of 379 patients, 30-day mortality was 21% (81 patients) and 1-year mortality was 28% (107 patients). There was no improvement in survival among octogenarian STEMI patients over the 11-year study period. Conclusion: The annual proportion of octogenarian STEMI patients increased significantly over the 11-year study period. Mortality among these high-risk patients was high and did not improve during the study period. Unfortunately, little is known about the optimal treatment of the elderly as they are underrepresented in many randomised clinical trials. Further studies into the optimal STEMI management strategy for the elderly are warranted.